THE IMPACT OF SCHOOL LITERACY MOVEMENT (GSL) ON THE LITERACY ABILITY OF THE FIFTH GRADERS AT SD NEGERI GUNUNG SARI, RAPPOCINI DISTRICT, MAKASSAR CITY - Syawaluddin, Ahmad; haedah, Nur (Universitas Pendidikan Ganesha, 2017)
This researchÂ was aimed at knowing the impact ofÂ (GLS) on the studentsâ literacy ability of the fifth graders atÂ SD Negeri Gunung Sari I,Â Â Rappocini district,Â Makassar city in the school year 2016/2017. The research approach used a quantitative approach with Pre-experimental Research design. The sample was selectedÂ with purposive sampling by choosing class V as experiment class with the total number ofÂ 66 students andÂ those who were present wereÂ 50 students. The techniques of data collection used in this research wereÂ test and documentation. The data collected from the literacy ability test result were then analyzed using descriptive statistical analysis and inferential statistical analysisÂ usingÂ sample t-test ofÂ Wilcoxon Test by using the test of two sides (two tailed test).Â To test the normality of the data distribution,Â Kolmogrov-Smirnov Normality Test was used with Asymp Sig. (2-Tailed)Â of 0.002 for pretest data and 0.003 for posttest data. Literacy ability on initial test (pretest) was in very satisfactory category with the mean of 83.99 and the literacy ability in the final test (posttest) was in very satisfactory category with the mean of 90.23. Hypothesis testing was done by usingÂ Wilcoxon Test Asymp Sig. (2-tailed) the value was 0.00 < 0.05. The conclusion of research based on the result of analysis showedÂ that there is an impactÂ of school literacy movement (GLS) on studentsâ literacy ability of fifth graders ofÂ SD Negeri Gunung Sari I inÂ RappociniÂ disctrict,Â Makassar city